Key Factors in the Market for Remanufactured Products - Subramanian, Ravi; Subramanyam, Ramanath (Manufacturing and Service Operations Management, 2012)
Measures to extend the economic lives of products—such as remanufacturing carried out by closed-loop supply chains—are receiving increased attention because of various economic and regulatory factors. In this paper, we examine drivers of price differentials between new and remanufactured products using data on purchases made on eBay. Our analysis shows that seller reputation significantly explains the price differentials between new and remanufactured products. We also find that products remanufactured by original equipment manufacturers or their authorized factories are purchased at relatively higher prices than products remanufactured by third parties. However, in the presence of these reputation signals (seller reputation and remanufacturer identity), we find that stronger warranties are not significantly associated with higher prices paid for remanufactured products. Our work contributes to the closed-loop supply chain research stream in operations management by empirically examining market factors that have not been studied before.